Genomic diversity of Neisseria gonorrhoeae Isolates in Kenya revealed by MLST, NG-MAST, and NG-STAR typing - Mary Wandia Kivata; Fredrick Lunyagi Eyase; Wallace Dimbuson Bulimo; Valerie Oundo; Esther Waguche; Wilton Mwema Mbinda; Margaret Wanjiku Mbuchi (PLoS ONE, 2026)
Background Surveillance of Neisseria gonorrhoeae strains, their antimicrobial resistance (AMR) profiles, and transmission dynamics is essential in the prevention and control of gonococcal infections. In Kenya, gonococcal molecular surveillance remains limited, leaving gaps in understanding circulating sequence types (STs). This study characterized Kenyan N. gonorrhoeae isolates using multiple molecular typing schemes. Methods Illumina MiSeq generated paired-end sequence reads prepared from 35 N. gonorrhoeae isolates recovered from males and females from four different regions in Kenya were analyzed. Assemblies were analyzed using PubMLST tools for multi-locus sequence typing (MLST) and the N. gonorrhoeae sequence typing for antimicrobial resistance (NG-STAR) scheme. Multi-antigen sequence typing (NG-MAST) was carried out using the NG-MAST database. Phylogenetic relationships were assessed using concatenated NG-STAR loci and core genome-based analyses. Results Twenty-two MLST STs were identified, including eight novel STs; ST-1932 was most frequent. NG-MAST revealed 29 STs, of which 26 were novel, with a newly described ST-19168 predominating in Nyanza region. NG-STAR identified 23 STs with variation across mtrR , penA , 23S rRNA , gyrA , parC, ponA , and porB. Phylogenetic analyses showed clustering of isolates into distinct groups with diverse AMR profiles. One cluster comprised isolates resistant to tetracycline and ciprofloxacin. No clear association was observed between MLST, NG-MAST, or NG-STAR types and specific AMR patterns. Conclusion Kenyan N. gonorrhoeae strains are genetically diverse, with high numbers of novel NG-MAST and MLST STs. The lack of regional clustering and varied AMR profiles suggests widespread transmission of heterogeneous gonococcal populations. These findings underscore the importance of strengthened genomic surveillance to inform gonorrhea control strategies in Kenya.